Intellectual property rights in the WTO and develoing countries - Watal, Jayashree (New Delhi Oxford University Press, 2001)
This volume provides a thorough and secure foundation on which international trade lawyers and business persons can build a global intellectual property regime that is both productive and fair.The volume includes detailed bibliographical references,making
Keywords: Intellectual property-India; Intellectual property-Developing countries; Copyright; Intangible property